Local Struggle for Accessing State Forest Property in a Montane Forest Village in Java, Indonesia - Maryudi, Ahmad; Krott, Max (ccsenet, 2012)
How local people can access state forests has become a central issue in forest resource management in Indonesia in recent years. This is because for most of the ‘modern history’ of forest management in the country, the forest resources have been at the monopoly of the state. In fact, there have been an increasing number of local people’ struggles for obtaining meaningful and legal access to the state forest resources in the country. In response to these, the forest administration has implemented a community forestry program. This paper aims to observe the transformation the people’s access to the forests, whether the community forestry program improve the access to the state forest resources. Employing the theory of access provided by Ribot and Peluso (2003), which defines access as the ability to benefit from a resource either legal or illegal, this paper finds that the community forestry program actually reduces the people’s access to the forests.